The fiduciary duties of agents / Nor Sa'adah Abd. Rahman - Abd. Rahman, Nor Sa'adah (Faculty of Law, 1985)
Sorretirres a person may not be able to act for himself. He may suddenly fall ill and be unable to walk, in which case he may enlist the help of another to my medicine for him. A houseowner who wishes to sell his home may require the help of a broker to sell his house for him. In such cases the person who acts for another is called an 'agent' and the person for whom or on whose behalf he acts is called the 'principal'. Agency therefore is the relationship which subsists between the principal and the agent who has been authorised to act for him or represent him in dealing with others. The relationship of principal and agent is a very conunon one in the modern day msiness world. The word Agency in a general way signifies the relationship that arises when one party uses another party to accomplish some purpose. There are three parties in an agency relationship, that is the party who authorizes another to do sorre business, the authorized party and the party with whom the msiness is transacted. The role and function of an agent is primarily to bring his principal and third party are brought into a contractual relationship he drops out. The agent does not become a party to the final arrangement. As in the case of Plantation Agency Sdn. Bhd. V Hi. Ari'ffin2 the court held that an agent is not personally liable in contract made by his principal